Evaluation of research group visibility, governance, and engagement in the top 500 global universities - Sawair, Faleh; Obeidat, Nathir; Ghazzawi, Hadeel (Frontiers in Education, 2025)
IntroductionThis exploratory quantitative study examines how the visibility of Research Groups (RGs) is structured, supported, and applied across the QS Top 500 universities (2026), reflecting a global shift toward research groups that serve society rather than solely academic prestige.MethodsThe analysis investigates the presence of formal governance frameworks, dedicated resources, visibility, interdisciplinary and international collaboration, student involvement, and external engagement with industry, government, and communities. It also compares patterns across global regions and between top-200 and 201–500 ranked universities.ResultsFindings revealed that while most universities host RGs with defined leaders, themes, and student participation, fewer than 40% employ formal policies or centralized oversight. Less than half of RGs build active partnerships beyond academia, secure external funding, or systematically share their achievements publicly. Mid-ranked universities display higher RG visibility and structured integration than many elite universities, which often rely on legacy laboratories and reputation rather than formal group frameworks.DiscussionUniversities are encouraged to strengthen RG policies, expand collaboration, and improve visibility to enhance both research impact and alignment with their broader missions.